Odpowiedzi

2009-09-12T00:15:16+02:00
A) 1⅞×(₋6) = 15/8 * (-6/1) = -90/8 = -11,25
b)-1⅕×2½ = -6/5 * 5/2 = -30/10 = -3
c)-1¾÷8 = -7/8 : 8/1 = -7/8 *1/8 = -7/64
d)1 ⅓×0,5 = 4/3 * 1/2 = 4/6 = 2/3
e)5,25÷(-1½) = 21/4 : (-7/3) = 21/4 * (-3/7) = 63/28 = 2,25
f)-1,5÷(-2⅓) = -11/2 :(-7/3) = -11/2 *(-3/7) = 33/14 = 2⁵/₁₄
g)-1¾+7⅕ = -7/4 + 36/5 = -35/20 + 144/20 = -109/20 = 5,45
h) -2⅜- 1/12 = -19/8 - 1/12 = -228/96 - 8/96 = -236/96 = -2¹¹/₂₄
i)-13,1 - 2,5 = -10,6
j) 17,21 - 20,03 = -2,82
k) -0,82 × (-0,3) = 0,246
l) -0,75 - (1⅔) = -3/4 - 5/3 = -9/12 - 20/12 = -11/12